2009
DOI: 10.4219/jeg-2009-862
|View full text |Cite
|
Sign up to set email alerts
|

Grade and Gender Differences in Gifted Students' Self-Concepts

Abstract: Gifted adolescents are poised to make important decisions that will determine the trajectory of their futures. A positive self-concept may lead to higher educational and career aspirations, whereas a poorer self-concept may negatively influence choices and outcomes. Research points to self-concept differences among gifted students of different ages (Chan, 2001) and genders (Hoge & McShreffrey, 1991; Li, 1988), with declining self-concept among females over time. The purpose of this study was to examine the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
3
8
0
3
Order By: Relevance
“…Furthermore, research on gender differences in self-concept typically shows that females score lower than males beginning in early adolescence, particularly in the areas of physical appearance and physical ability (Worrell, Roth, & Gabelko, 1998). With a sample of gifted adolescents, Rudasill, Capper, Foust, Callahan, and Albaugh (2009) found lower self-concept among females in almost all dimensions of self-concept. However, some researchers argue gender differences in self-concept among adolescents are small and lack meaning (e.g., Crain & Bracken, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research on gender differences in self-concept typically shows that females score lower than males beginning in early adolescence, particularly in the areas of physical appearance and physical ability (Worrell, Roth, & Gabelko, 1998). With a sample of gifted adolescents, Rudasill, Capper, Foust, Callahan, and Albaugh (2009) found lower self-concept among females in almost all dimensions of self-concept. However, some researchers argue gender differences in self-concept among adolescents are small and lack meaning (e.g., Crain & Bracken, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Se observó que once de estos niños y niñas se perciben como buenos estudiantes, siete mostraron alto compromiso con la tarea y seis fueron nominados por sus maestros. Como un dato interesante, resultó que el autoconcepto académico permitió incluir a un mayor número de estudiantes, lo cual confirma lo reportado por Hoge y Renzulli (2007), Mönks (1999), Moritz et al, (2009), Pomar, (2001, Preckel et al, (2008) Título: La hormiga Título: La mujer pájaro Lo anterior permite afirmar que la creatividad es un aspecto importante a desarrollar en la infancia, pues como señalaron Guilford (1977) y Torrance (1977) forma parte de las operaciones intelectuales relacionadas con desarrollo del pensamiento divergente. Por su parte, Betancourt y Valadez (2005) indicaron que esta capacidad es relevante en la vida actual, debido a que permite que las personas se enfrenten a los problemas que se encuentran de manera cotidiana y que se puede favorecer conforme avanza la edad y el grado escolar a través de las distintas experiencias educativas y del contexto en el que se desenvuelven los niños y las niñas.…”
Section: Resultados Y Su Análisisunclassified
“…Se encontraron las estimaciones mínimas, máximas, medias, la desviación estándar y el percentil 75 que, de acuerdo con diversos autores como Renzulli Además, con base en la evidencia empírica se estableció que era indispensable considerar para todos los niños y niñas con aptitud sobresaliente las puntuaciones de percentil 75 en las variables de inteligencia y creatividad (Espinoza y Reyes Fiz, 2008;Gagné, 2010, Heller y Hany, 2004Manzano et al, 2010;Mönks y Van Boxtell, 1992;Liu, 2007;Piirto, 1999;Renzulli, 2011;Sternberg, 1990;Valadez et al, 2006;Zacatelco, 2005). Y por lo menos este mismo nivel en alguno de los otros tres factores: compromiso con la tarea (Gottfried, Gottfied, Cook y Morris, 2005;Moritz et al, 2009;Zacatelco y Chávez, 2010), autoconcepto académico (Heller y Hany, 2004;Mönks y Van Boxtell, 1992;Piirto, 1999;Renzulli, 2011) y/o nominación del maestro (Mönks y Van Boxtell, 1992;Valadez et al, 2006;Zacatelco, 2005; Zacatelco, Chávez y Acle, 2010).…”
Section: Procedimientounclassified
“…It is a widespread conclusion that gifted students display a higher academic self-concept than non-gifted students (Al-Srour et al, 2016;Hoogeveen et al, 2009;McCoach & Siegle, 2003;Rost & Hanses, 2000;Sarouphim, 2011;Wirthwein et al, 2019; but see Callahan, 2004; see Table 4) and that the academic selfconcept is positively correlated with global self-concept (Frances et al, 2000;Plucker & Stocking, 2001). Furthermore, other studies found a slight sex bias towards the trend that girls had slightly higher self-concept scores than boys (Lewis & Knight, 2000;Rudasill et al, 2009).…”
Section: Differences In Self-concept Between Gifted and Non-gifted Stmentioning
confidence: 92%